Cellular and Molecular Connections Between Bone Fracture Healing and Exosomes - Lv, S; Wang, G; Dai, L; Wang, T; Wang, F (Physiological research, 2023)
Fracture healing is a multifaceted process that requires various phases and intercellular interactions. In recent years, investigations have been conducted to assess the feasibility of utilizing exosomes, small extracellular vesicles (EVs), to enhance and accelerate the healing process. Exosomes serve as a cargo transport platform, facilitating intercellular communication, promoting the presentation of antigens to dendritic cells, and stimulating angiogenesis. Exosomes have a special structure that gives them a special function, especially in the healing process of bone injuries. This article provides an overview of cellular and molecular processes associated with bone fracture healing, as well as a survey of existing exosome research in this context. We also discuss the potential use of exosomes in fracture healing, as well as the obstacles that must be overcome to make this a viable clinical practice.
Keywords: extracelulární vezikuly; mezenchymální kmenové buňky; Extracellular Vesicles; exozómy; hojení fraktur; Cell Communication; Mesenchymal Stem Cells; mezibuněčná komunikace; Exosomes; Fracture Healing